Investigation of a Cu/Pd Bimetallic System Electrodeposited on Boron-Doped Diamond Films for Application in Electrocatalytic Reduction of Nitrate - Jorge T. Matsushima; Valéria C. Fernandes; Andrea B. Couto; Maurício R. Baldan; Neidenêi G. Ferreira (International Journal of Electrochemistry)
The Cu/Pd bimetallic system electrodeposited on boron-doped diamond (BDD) films for application, as electrode material in the electrochemical reduction of nitrate was studied. The electrochemical behavior of Cu, Pd, and Cu/Pd bimetallic system was evaluated by cyclic voltammetry. From these results, the formation of the Cu/Pd composite was verified. In addition, Cu with different phases and a Cu/Pd phase in the composite were obtained. Morphological analysis by scanning electron microscopy (SEM) revealed a homogeneous distribution of Cu/Pd bimetallic particles with intermediary dimensions compared to those observed in Cu or Pd electrodeposits separately. These composites were tested as electrocatalysts for nitrate reduction in Britton-Robinson buffer solution (pH 9). Electrochemical measurements showed that composites with higher Cu content displayed the best electrocatalytic activity for nitrate reduction, and the Cu/Pd phase in the bimetallic system served to improve the Cu adherence on BDD electrode.